Typhus Fever: An uncommon childhood infectionReport of a Case from Northern Region of Bangladesh - Basak, Ranjit; Islam, Nawshin (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2013)
Typhus fever is not a common problem in childhood and mostly it is misdiagnosed. In this child, the clinical diagnosis was typhoid fever. On admission the child was presented with long standing fever with splenomegaly supported by significant widal test. Despite appropriate treatment, the patient was not responding. Later, most common differential diagnoses were thought to be tuberculosis and typhus fever. Finally, a co-infection of typhoid and typhus fever was discovered. This uncommon presentation should be taken into consideration in difficult to treat prolonged fever in children. DOI: http://dx.doi.org/10.11566/cmoshmcj.v12i2.40 Chatt Maa Shi Hosp Med Coll J 2013; 12(2): 49-51